2018
DOI: 10.2196/resprot.9793
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Directed Mobile Intervention (WaznApp) to Promote Weight Control Among Employees at a Lebanese University: Protocol for a Feasibility Pilot Randomized Controlled Trial

Abstract: BackgroundOverweight and obesity have become major health problems globally with more than 1.9 billion overweight adults. In Lebanon, the prevalence of obesity and overweight is 65.4% combined. Risk factors of obesity and overweight are preventable and can be addressed by modifications in the environment and in an individual’s lifestyle. Mobile technologies are increasingly used in behavioral, self-directed weight management interventions, providing users with additional opportunities to attain weight control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
(97 reference statements)
0
13
0
1
Order By: Relevance
“…A summary and detailed description of the study characteristics are shown in Table 1 and Multimedia Appendix 3 [ 25 , 26 , 29 - 47 ] and Multimedia Appendix 4 [ 25 , 26 , 29 - 37 , 39 - 47 ]. The chatbot programs included Wakamola [ 30 - 32 ], WaznApp [ 33 ], WeightMentor [ 25 ], SWITCHes [ 34 ], MobileCoach [ 35 ], PathMate2 [ 36 ], and Lark Weight Loss Health Coach AI [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…A summary and detailed description of the study characteristics are shown in Table 1 and Multimedia Appendix 3 [ 25 , 26 , 29 - 47 ] and Multimedia Appendix 4 [ 25 , 26 , 29 - 37 , 39 - 47 ]. The chatbot programs included Wakamola [ 30 - 32 ], WaznApp [ 33 ], WeightMentor [ 25 ], SWITCHes [ 34 ], MobileCoach [ 35 ], PathMate2 [ 36 ], and Lark Weight Loss Health Coach AI [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of mobile apps to facilitate behavior change has shown promising results in providing rich context information including an objective assessment of physical activity level and information on the emotional and physiological state of the person. 15,25 Current health coaching systems integrate artificial intelligence (AI)-based conversational agents powered with machine learning and natural language understanding. 23,31,32 Such systems are flexible and can respond to users' requests.…”
Section: Related Workmentioning
confidence: 99%
“…11 The rise in artificial intelligence gave birth to messaging applications that run a conversational agent to handle some tasks. Such applications are already used in diet management, [12][13][14] physical activity promotion, 15 medication adherence, 16 and mental wellbeing promotion. 17 In addition, users, including the elderly, are familiar with messaging applications due to their low associated learning curve.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar que el incremento del uso de las TICS en las últimas décadas ha tomado auge generando un aumento progresivo de las horas en comportamiento sedentario, estas herramientas también contribuyen Actividad física como estrategia para la prevención y manejo de la obesidad Yaneth Herazo-Beltrán, Yisel Pinillos-Patiño, Lilibeth Sánchez-Guette, Maricela Torres-Anaya y Luisa Galeano Muñoz 175 a promover estilos de vida saludable. En la actualidad se cuenta con aplicaciones que educan y ayudan determinar el gasto calórico, a partir de la dieta y nivel de actividad física del sujeto, en este sentido, las intervenciones están encaminadas al seguimiento del uso de aplicaciones para teléfono móviles de tecnología android y apple, como podómetros, y contadores de calorías según ingesta diaria (Bardus, Hamadeh, Hayek, y Al Kherfan, 2018). Este tipo de estrategias permiten el automonitoreo y la autogestión hacia el cambio, en consecuencia, las intervenciones que proponen el uso de la tecnología para el control de peso, pueden llegar a ser efectivas, debido a que los sujetos que registran su peso a diario o cada semana, tienden a ser más exitoso en la disminución del IMC, así, se puede aseverar que el autocontrol mejora la conciencia de la ingesta calórica, lo que se puede ver reflejado en la disminución del peso corporal (Dunstan, Healy, Sugiyama, y Owen, 2010;Bardus et al, 2018;Holliday et al, 2018).…”
Section: Uso De La Tecnologíaunclassified